(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
There is unanimity in the scientific community regarding the inevitable reformsto be undertaken in order to sustain the National Health System (NHS),however, there are notable differences in the content of these reforms as consequenceof different value judgments from the persons or institutions that formulatethem: what politics should be implemented in order that the S.N.S. wereworking with higher dose of efficiency and efficiency and, therefore, they couldcontribute to sustainability?The aim of this work is to analyze the innovative reforms being carried out inSpain from the 90s and if they are applicable to the entire NHS with the intentionof make the provision of public health services more effective and efficient.